HOUGH-transform based automatic invariant recognition of metallic corner-fasteners. - Montenegro Joo, Javier (2007)
The Polar Hough Transform has been used to create a system for rotation, translation and sizescaling automatic invariant pattern recognition of polygonal objects, and it has been successfully applied to the invariant recognition of L-shaped metallic corner-fasteners. Since the performance of the developed system is autonomous it may be applied to automatic quality control and automatic classification in the industry.